The Telemark Breast Score: a Valid Method for Evaluation of Outcome after Breast Surgery. (February 2017) - Begic, Anadi; Stark, Birgit
Abstract : Background: "Telemark Breast Score" (TBS) has been developed at Telemark Hospital in Norway for evaluation of results after breast surgery based on standardized patients' photographs taken as a part of daily routine. Its reliability has recently been tested and approved. The external validity of the TBS was assessed by matching its data against the internationally recognized Breast-Q (BQ) questionnaire as a further step to study the validity of this new tool. Methods: The ideal distribution of breast volume is 45% of the total volume above and 55% below the nipple, and a 40° slope line at the upper pole. TBS makes the evaluation of these parameters of breast aesthetics more explicit. The method has been tested on photographs from 31 patients operated on for breast cancer with the Deep Inferior Perforator Flap. The evaluation was done by an independent experienced plastic surgeon earlier participating in the test–retests. The external validity of TBS was investigated against domains 1 and 3 of the BQ reconstruction module. The concordance between ratings was analyzed. Results: Concordance between TBS items and BQ domain 1 items regarding patient satisfaction, and between TBS items and BQ domain 3 items regarding how the patient experienced the outcome of breast reconstruction was relatively high except for 6 comparisons where we could not statistically ensure that more pairs were concordant than discordant. A total of 178 comparisons appeared to be concordant. This means that for all other comparisons, there was a preponderance of pairs of concordant observations, which indicates that measurements from the 2 instruments follow each other. Conclusion: The present data indicate that the TBS can be recommended as a valid tool to professionals for assessment of the outcome after breast reconstruction.